The Effect of Giving Cucumber (Cucumis sativus) Juice on Blood Pressure in Stage 1 Hypertension Patients in Cimahi Public Health Center - Tria Firza Kumala; Rita Fitria; Susilawati Susilawati; Ira Mehara; Asep Badru Jamaludin; Diwa Agus Sudrajat (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Background: One of the management of hypertension is with herbal medicine, such as cucumber juice, because cucumber contains a lot of potassium and water, a diuretic that can lower blood pressure. Aim: This study aimed to determine the effect of cucumber juice on blood pressure in patients with stage 1 hypertension. Method: The research design used was (a quasi-experimental design) with the design using the Non-Equivalent Control Group. A total of 28 people whose blood pressure was measured consisted of 14 people in the intervention group giving cucumber juice and 14 in the control group without giving cucumber juice. Results: The study’s mean systolic blood pressure in the control and intervention groups ranged above 130 mmHg and 80 mmHg for diastolic. After the intervention procedure, the mean systolic and diastolic blood pressure in the intervention group decreased to 120.71 mmHg (systolic) and 76.43 mmHg (diastolic). In contrast, the control group’s systolic and diastolic blood pressure was relatively stable. The Independent t-test result showed a significant p-value (< 0.05). Meanwhile, in the control group, a p-value of (> 0.05) was obtained, meaning there was no change in blood pressure in the control group. Conclusion: This study showed that cucumber juice affects blood pressure. Based on the study’s result, nurses need to maximize hypertension control by giving education to constantly consume anti-hypertensive drugs along with herbal medicine such as cucumber juice.